2019
DOI: 10.1016/j.rmed.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mepolizumab in severe eosinophilic asthma according to omalizumab eligibility

Abstract: Background: Patients with severe asthma can present with overlapping eosinophilic and allergic phenotypes, which makes it challenging when deciding which biologic therapy is most appropriate to reduce exacerbations and help achieve asthma control. Objective: This post hoc meta-analysis evaluated the efficacy of the licensed dose of mepolizumab (100 mg administered subcutaneously [SC]) versus placebo in patients with severe eosinophilic asthma (SEA), according to omalizumab eligibility and associated allergic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
(47 reference statements)
4
22
0
Order By: Relevance
“…Mepolizumab, a marketed human antiinterleukin-5 monoclonal antibody for patients with severe eosinophilic asthma [19], has been evaluated in two separate studies for patients who either received [20] or were qualified at study entry [21] to receive omalizumab treatment. In a post hoc analysis of the phase III MENSA trial [22], patients who received omalizumab had a 57% exacerbation rate reduction with mepolizumab vs. placebo (compared with 47% for those who did not receive omalizumab) [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mepolizumab, a marketed human antiinterleukin-5 monoclonal antibody for patients with severe eosinophilic asthma [19], has been evaluated in two separate studies for patients who either received [20] or were qualified at study entry [21] to receive omalizumab treatment. In a post hoc analysis of the phase III MENSA trial [22], patients who received omalizumab had a 57% exacerbation rate reduction with mepolizumab vs. placebo (compared with 47% for those who did not receive omalizumab) [20].…”
Section: Discussionmentioning
confidence: 99%
“…In a post hoc analysis of the phase III MENSA trial [22], patients who received omalizumab had a 57% exacerbation rate reduction with mepolizumab vs. placebo (compared with 47% for those who did not receive omalizumab) [20]. In a post hoc meta-analysis of data from the phase III MENSA [22] and MUSCA [23] trials, mepolizumab reduced exacerbation rates vs. placebo by 57% and 55% for patients who were qualified or unqualified for omalizumab (based on prescribing and dosing criteria), respectively [21]. Together with our findings, this supports the use of agents that target eosinophils directly A limitation of this study was the small numbers of patients for the different subgroups, which restricted interpretation of the findings with no consistent trends.…”
Section: Discussionmentioning
confidence: 99%
“…For the use of mepolizumab in allergic asthma in a licensed dose, an open multicentre, open‐label, single‐arm study showed clinically significant improvements in asthma control, health status and exacerbation rate 104 . The post hoc meta‐analysis of two phase 3 studies showed efficacy of mepolizumab regardless of allergic characteristics or omalizumab eligibility 105 . Recent reports show that both mepolizumab and reslizumab can control severe asthma patients that failed to respond to omalizumab 106 .…”
Section: Key Recommendations (Biologicals Are Mentioned In Alphabeticmentioning
confidence: 99%
“…Dupilumab is recommended in adults and paediatric population 12-to 17-years old with uncontrolled severe T2 asthma* in spite of optimal controller treatment to: Dupilumab demonstrated a good safety profile; however, longer term data (up to 2 years) are extrapolated from atopic dermatitis studies and careful reporting of all drug-related adverse events is recommended For the use of mepolizumab in allergic asthma in a licensed dose, an open multicentre, open-label, single-arm study showed clinically significant improvements in asthma control, health status and exacerbation rate 104. The post hoc meta-analysis of two phase 3 studies showed efficacy of mepolizumab regardless of allergic characteristics or omalizumab eligibility 105. Recent reports show that both mepolizumab and reslizumab can control severe asthma patients that failed to respond to omalizumab 106.…”
mentioning
confidence: 99%
“…However, both trials and real-life studies [5, 6] analyzed subjects with severe eosinophilic asthma regardless of allergic and nonallergic pathways leading to eosinophilic inflammation. Recently, post hoc meta-analysis and real-life studies have shown mepolizumab effectiveness in subjects affected by SAEA identified by using omalizumab eligibility or previous omalizumab treatment failure criteria [7, 8]. However, these studies compared eligible with ineligible omalizumab patients, although the latter may also include both individuals with seasonal allergies and high allergy-induced IgE levels.…”
Section: Introductionmentioning
confidence: 99%